'Provincialising' the Belt and Road Initiative: Theorising with Chinese narratives of the 'Digital Silk Road' (数字丝绸之路). (26th October 2021) - Woon, Chih Yuan
Abstract : This paper reflects on how the Belt and Road Initiative (BRI) can contribute to more cosmopolitan forms of theory‐making and the diversification of knowledges. It focuses on emerging Chinese narratives of the Digital Silk Road (DSR) that cast the initiative as emblematic of an improved BRI 2.0 in the (post‐)pandemic era. With subterranean fibre‐optic cables and satellite systems constituting important components of the DSR, I argue that these Chinese discourses fundamentally expose the 'horizontal' bias in infrastructure debates, thereby forcing an analytical re‐orientation towards the notion's volumetric possibilities. Reconceptualising infrastructures in volumetric terms opens up opportunities for interrogating issues of representational politics, power and sovereignty that matter for the DSR and beyond. Using Chinese perspectives of the DSR for the purpose of theory‐building, however, does not equate to endorsing Sinocentrism or privileging the BRI as a totalising framework for interpreting the world. Rather, it signifies an effort to 'provincialise' the BRI – ensuring that different voices and subjectivities can co‐exist in the ongoing and unfinished project of rethinking/reconstructing the BRI.